Estrategias metodológicas en la docencia de la asignatura de matemáticas y su incidencia en el proceso educativo con los estudiantes de educación básica superior del Centro Educativo Matriz 2 Plantel Central Enrique Mora Sares de la ciudad de Machala, provincia de El Oro periodo 2014 - 2015. - Llinín Yumiceba, Teresa Fabiola (2015)
This research gives us the opportunity to identify learning strategies in the mathematics that can be developed using these as part of the development of classes, It lets us know the importance of teaching resources in the teaching-learning process and reflected in the academic performance of students in this course eighth , ninth and tenth year of basic education in the school Enrique Mora Sares city results Machala .